Experimental rearing of the small spruce bark beetle Ips amitinus (Eichhoff, 1872) (Coleoptera: Curculionidae, Scolytinae) on aboriginal Siberian coniferous species - Nikita A. Smirnov; Ivan A. Kerchev (Acta Biologica Sibirica)
The possibility of development of the invasive European species Ips amitinus (Eichhoff, 1872) on various coniferous species of Siberia was analyzed under laboratory conditions. The first experiment was carried out on fresh sections of the trunks of Abies sibirica Ledeb., Picea obovata Ledeb., Larix sibirica Ledeb., and Pinus sylvestris L., with the possibility for beetles to choose one of the four proposed tree species. The second experiment was conducted on the same tree species, but without the option for the beetles to choose the species for food. The third experiment consisted in breeding I. amitinus on Pinus pumila (Pall.) Regel. In the first two experiments on P. sylvestris, one generation of beetles developed successfully. It was found that P. sylvestris is the most favorable for the settlement and development of I. amitinus in the West Siberian invasion region followed by P. sibirica. On Siberian fir, Siberian spruce and Siberian larch, bark beetles died in galleries without forming nests. In the third experiment, successful beetle colonization of the branches was observed. In all the experiments, the demographic indicators of the pest were determined (settlement density, the number of parental beetles, the number of emerged beetles, offspring/parent ratio per unit area). These indicators were compared with those obtained on P. sibirica. A high probability of further expansion of the small spruce bark beetle both westward and eastward has been established.